German Energiewende and the Heating Market - Impact and Limits of Policy - Klaas Bauermann (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
The German Energiewende envisages achieving a climate-neutral building stock in 2050 by means of two major pillars of regulation: First, residential buildings should consume 80% less primary energy and, second, the remaining energy demand should be covered primarily with renewables. This paper simulates the future heating market in Germany under different policy scenarios in order to evaluate the impact and limits of recent and conceivable heating market policy. The investigation is based upon a dual model approach, linking a residential heating model to a discrete choice model for the heating system purchase decision. The major finding is that current âregulations will not be suitable for meeting government targets. Carbon emission reductions in scenarios assuming current regulation nearly equal those where there is no regulation. In terms of economic efficiency, all calculated policy alternatives perform better than the regulation currently in place. The model results highlight two policy implications. First, rising renewable requirements deliver better results at lower costs. Second, renewable obligations for heating systems must include the existing building stock in order to achieve the postulated political targets.
Keywords: E27; E61; H21; O18; O38; C35; C53; 330; Residential Heating Market; Policy Evaluation; Decarbonisation; Discrete Choice